Pengembangan Media Ajar Tutorial Elektronik Mengenai Materi Peta Kelas Xii-Is Sekolah Menengah Atas - Setia Aji, Ghafuur, M. Amin Sunarhadi, S.Si., M.P (2015)
The ability of teachers is diverse, one of the teachers' pedagogical abilities are able to develop and utilize instructional media. Media in learning has an important role. In the modern era of the many teachers who have not been able to develop purely electronic instructional media, averaging some teachers still use old ways / methods of teaching time. The goal of this study was able to determine criteria for the product development of the electronic media tutorial teaching materials XII class map-IS. The method used in this research is the development of research. The study was conducted at 2 Surakarta Muhammadiyah high school class XII with the subject and object of research is the lesson tutorial teaching media geografii. Adalam methods of data collection are observation, interviews, and documentation. Methods of data analysis with quantitative descriptive technique. Based on the analysis of the results and discussion can be deduced as follows. Criteria for the development of electronic media for learning tutorial teaching subjects geography as follows: Media teaching full color electronic tutorials, instructional media tutorial existing electronic music, media teaching text tutorial existing electronics, electronic tutorial teaching media that is motivation. Development of instructional media electronic tutorials on the map, explaining the definition of a map, a way of making maps from the beginning to be a handout in the map are the components of the map.